Crosstalk Between Ethylene and Abscisic Acid During Changes in Soil Water Content Reveals a New Role for 1-Aminocyclopropane-1- Carboxylate in Coffee Anthesis Regulation - López, Marlon Enrique; Silva Santos, Iasminy; Marquez Gutiérrez, Robert; Jaramillo Mesa, Andrea; Cardon, Carlos Henrique; Espíndola Lima, Juliana Maria; Almeida Lima, André; Chalfun-Junior, Antonio (Frontiers in Plant Science, 2022)
Coffee (Coffea arabica L.) presents an asynchronous flowering regulated by an endogenous and environmental stimulus, and anthesis occurs once plants are rehydrated after a period of water deficit. We evaluated the evolution of Abscisic Acid (ABA), ethylene, 1-aminocyclopropane-1-carboxylate (ACC) content, ACC oxidase (ACO) activity, and expression analysis of the Lysine Histidine Transporter 1 (LHT1) transporter, in the roots, leaves, and flower buds from three coffee genotypes (C. arabica L. cv Oeiras, Acauã, and Semperflorens) cultivated under field conditions with two experiments. In a third field experiment, the effect of the exogenous supply of ACC in coffee anthesis was evaluated. We found an increased ACC level, low ACO activity, decreased level of ethylene, and a decreased level of ABA in all tissues from the three coffee genotypes in the re-watering period just before anthesis, and a high expression of the LHT1 in flower buds and leaves. The ethylene content and ACO activity decreased from rainy to dry period whereas the ABA content increased. A higher number of opened and G6 stage flower buds were observed in the treatment with exogenous ACC. The results showed that the interaction of ABA-ACO-ethylene and intercellular ACC transport among the leaves, buds, and roots in coffee favors an increased level of ACC that is most likely, involved as a modulator in coffee anthesis. This study provides evidence that ACC can play an important role independently of ethylene in the anthesis process in a perennial crop.